Family systems approach to attachment relations, war trauma, and mental health among Palestinian children and parents. (15th December 2017) - Punamäki, Raija-Leena; Qouta, Samir R.; Peltonen, Kirsi
ABSTRACT: Background : Trauma affects the family unit as a whole; however, most existing research uses individual or, at most, dyadic approaches to analyse families with histories of trauma. Objective : This study aims to identify potentially distinct family types according to attachment, parenting, and sibling relations, to analyse how these family types differ with respect to war trauma, and to explore how children's mental health and cognitive processing differ across these family types. Method: Participants included Palestinian mothers and fathers ( N = 325) and their children (one per family; 49.4% girls; 10–13 years old; mean ± SD age = 11.35 ± 0.57 years) after the Gaza War of 2008–2009. Both parents reported their exposure to war trauma, secure attachment availability, and parenting practices, as well as the target child's internalizing and externalizing symptoms [Strengths and Difficulties Questionnaire (SDQ)]. Children reported their symptoms of post-traumatic stress disorder (on the Children's Revised Impact Event Scale), depression (Birleson), and SDQ, as well as their post-traumatic cognitions (Children's Post Traumatic Cognitions Inventory). Results: A cluster analysis identified four family types. The largest type reflected secure attachment and optimal relationships (security and positive family relationships, 36.2%, n = 102), and the smallest exhibited insecurity and problematic relationships (insecurity and negative family relationships, 15.6%; n = 44). Further, families with discrepant experiences (23.0%; n = 65) and moderate security and neutral relationships (25.2%; n = 71) emerged. The insecurity and negative relationships family type showed higher levels of war trauma; internalizing, externalizing, and depressive symptoms among children; and dysfunctional post-traumatic cognitions than other family types. Conclusion: The family systems approach to mental health is warranted in war conditions, and therapeutic interventions for children should, thus, also involve parents and siblings. Knowledge of unique family attachment patterns is fruitful for tailoring therapeutic treatments and preventive interventions for war-affected children and families.